Nitrophenylcarbenes. Part I. The catalytic and photolytic decomposition of α-diazo-3-nitrotoluene in the presence of olefins - Goh, S.H. (Royal Society of Chemistry, 1971)
The decomposition of α-diazo-3-nitrotoluene by zinc halides in the presence of olefins gave cyclopropane adducts in moderate yields. The addition of the carbenoid intermediate to unsymmetrically substituted olefins is syn-stereoselective. The free carbene species generated by photolysis also added readily to olefins. Non-stereospecific cyclopropane adducts and olefinic products were also formed, as a result of the involvement of both singlet and triplet 3-nitrophenylcarbenes.